Legal Issues of State Financial Status in State-Owned Enterprises of the Holding Company Indonesian Mining Industry (MIND ID) - Muhammad Juang Rambe (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
Holding company Mining Industry Indonesia (MIND ID) is one of the state-owned holding companies in Indonesia. MIND ID is a holding company in the mining sector which was formed based on Government Regulation Number 47 of 2017. The state financial status of state-owned enterprises and or subsidiaries of state-owned enterprises is still a matter of debate. There is an assumption that a state-owned company and/or its subsidiaries have state finances, but another opinion states that there is no state finance in the state-owned company but rather becomes the finances of the state-owned company. Supreme Court Decisions No. 21 P/HUM/2017 and No. 7 P/HUM/2018 principally state that a subsidiary of a SOE in a SOE holding structure does not turn into an ordinary Limited Liability Company, but remains a SOE. Then one of the cases of financial losses in state-owned enterprise subsidiaries as examined and tried in the Pangkal Pinang District Court Decision, namely in Decree Number 1 / Pid.Sus-TPK / 2021 / PN Pgp. The case in question is a case of alleged corruption in a subsidiary of the SOE Holding Company Mining Industry Indonesia (MIND ID), namely PT Timah, Tbk. In this decision, the panel of judges held that the SOE subsidiary, in this case, PT Timah, Tbk in the holding company of the Indonesian Mining Industry (MIND ID) is not a state-owned enterprise but a national private company. The consideration of the panel of judges in Decision Number 1/Pid.Sus-TPK/2021/PN Pgp regarding the financial status of the state in state-owned subsidiaries is different from the consideration of the panel of judges in the review decision in Decision Number 7 P/HUM/2018 Jo. Decision No. 21 P/HUM/2017.